Diskursus Kritik Naratif Sebagai Metode Hermeneutis Biblis Menurut Kajian Teolog Biblika - Marde Christian Stenly Mawikere; Sudiria Hura (Program Studi Teologi, Fakultas Teologi, Institut Agama Kristen Negeri Manado, 2023)
This article describes narrative criticism as a Scripture hermeneutical method according to a literature review as a result of research by several Biblical theologians. As for the substance of the biblical literature and the theologians' perceptions reviewed, the researchers selected randomly. This study uses a qualitative method built by a literature study that is in sync with the research problem. The final result of this study shows how theologians express their perception of narrative criticism as a method of biblical interpretation that emphasizes the historical story of God's salvation. The final results also show that with various perceptions, all theologians recognize the benefits of narrative interpretation of the Bible as an important part of explaining God's initiative in revealing Himself and communicating with humans. Researchers also point to a variety of strengths and weaknesses in the theologians' perceptions of the research problem. This will provide opportunities and possibilities for further research in this field, both scientifically and practically.